ALFABURST: A realtime fast radio burst monitor for the Arecibo telescope - Chennamangalam, J; Karastergiou, A; MacMahon, D; Armour, W; Cobb, J; Lorimer, D; Rajwade, K; Siemion, A; Werthimer, D; Williams, C (World Scientific Publishing Co, 2017)
Fast radio bursts (FRBs) constitute an emerging class of fast radio transient whose origin continues to be a mystery. Realizing the importance of increasing coverage of the search parameter space, we have designed, built, and deployed a realtime monitor for FRBs at the 305-m Arecibo radio telescope. Named `ALFABURST', it is a commensal instrument that is triggered whenever the 1.4 GHz seven-beam Arecibo L-Band Feed Array (ALFA) receiver commences operation. The ongoing commensal survey we are conducting using ALFABURST has an instantaneous field of view of 0.02 sq. deg. within the FWHM of the beams, with the realtime software configurable to use up to 300 MHz of bandwidth. We search for FRBs with dispersion measure up to 2560 cm^-3 pc and pulse widthsranging from 0.128 ms to 16.384 ms. Commissioning observations performed over the past few months have demonstrated the capability of the instrument in detecting single pulses from known pulsars. In this paper, I describe the instrument and the associated survey.